2009
DOI: 10.1093/scan/nsn050
|View full text |Cite
|
Sign up to set email alerts
|

Highly religious participants recruit areas of social cognition in personal prayer

Abstract: We used functional magnetic resonance imaging (fMRI) to investigate how performing formalized and improvised forms of praying changed the evoked BOLD response in a group of Danish Christians. Distinct from formalized praying and secular controls, improvised praying activated a strong response in the temporopolar region, the medial prefrontal cortex, the temporo-parietal junction and precuneus. This finding supports our hypothesis that religious subjects, who consider their God to be 'real' and capable of recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
198
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(226 citation statements)
references
References 38 publications
16
198
0
4
Order By: Relevance
“…Han et al (2008) showed that personal trait judgments regarding the self or public persons showed signifi cantly greater activity of the mid-dorsal medial frontal cortex in Christian than in non-religious subjects. Moreover, it was reported that religious participants recruited brain areas during personal prayer that had been implicated in social cognition such as the medial dorsal frontal cortex, the precuneus, and the temporoparietal junction (Schjoedt et al , 2009 ). This is of note because there is a considerable neuroanatomical intersubject variability concerning the brain areas activated in relation to religiosity (Kapogiannis et al , 2009 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Han et al (2008) showed that personal trait judgments regarding the self or public persons showed signifi cantly greater activity of the mid-dorsal medial frontal cortex in Christian than in non-religious subjects. Moreover, it was reported that religious participants recruited brain areas during personal prayer that had been implicated in social cognition such as the medial dorsal frontal cortex, the precuneus, and the temporoparietal junction (Schjoedt et al , 2009 ). This is of note because there is a considerable neuroanatomical intersubject variability concerning the brain areas activated in relation to religiosity (Kapogiannis et al , 2009 ).…”
Section: Resultsmentioning
confidence: 98%
“…Schjoedt et al (2009) Personal prayer in religious subjects 8 20 50 Han et al (2008) Christian self-judgment 8 27 35 Sommer et al (2010) False belief attribution 4 34 40 Stern et al (2010) Greater uncertainty in sampling 6 33 30 Rothmayr et al (2011) Belief reasoning + inhibitory control 10 36 44 Beauregard and Paquette (2006) Mystical experience -11 52 13 Knutson et al (2007) Combined race and gender associations 20 51 9 Kapogiannis et al (2009) God ' s perceived involvement 9 66 6 Unauthenticated Download Date | 5/12/18 11:38 PM For the ' process of believing ' as it might appear in a religious or secular manner, we would like to coin the neologism ' credition ' . Credition is conceived as a psychological term in analogy to emotion and cognition that denotes the mental activity related to what we call ' he/she believes ' (Angel , 2006(Angel , , 2012.…”
Section: Theoretical Considerations Of Belief Processesmentioning
confidence: 99%
“…Second, based on reports that individuals pray to gain subjective strengthening (Janssen et al, 1990), we investigated whether the extent to which individuals try to find strength during praying would mediate the hypothesized effect. Finally, previous research showed that (a) people interpret praying as a social interaction with God (Bremner, Koole, & Bushman, 2011;Schjoedt, Stødkilde-Jørgensen, Geertz, & Roepstorff, 2009), and (b) even brief social interactions can trigger cognitive resources and enhance executive control (Ybarra et al, 2008). We therefore investigated engagement in social interaction as a third potentially mediating factor.…”
Section: Introductionmentioning
confidence: 99%
“…Supernatural agents appear to be represented via mechanisms supporting everyday social cognition: God, gods, angels, demons, and spirits are conceptualized as persons (Barrett, 2000;Boyer, 2003). Correspondingly, brain areas associated with representing the minds of other people are activated when imagining God's mind (Kapogiannis et al, 2009;Schjødt, Stodkilde-Jorgensen, Geertz, & Roepstorff, 2009). In convergent psychobiological evidence, endogenous oxytocin -a hormone associated with social bondingcorrelates with self-reported spirituality (Holbrook, Hahn-Holbrook, & Holt-Lunstad, 2015).…”
Section: Introductionmentioning
confidence: 99%